Strategi pemasaran digital: Adaptasi strategis di tengah perubahan lingkungan bisnis - Marzuki, Mochamad Fuad (Maliki Interdisciplinary Journal, 2025)
In the increasingly dynamic digital era, companies must adapt quickly to remain relevant and successful. Digital marketing strategies have become a highly effective strategy to implement in order to achieve business goals, especially in increasing visibility, market expansion, and broadening sales reach. Digital platforms such as social media, email, and search engines have become the primasssry means of consumer interaction with products and services. Technological advantages such as lower costs, faster transactions, and easier access to information make consumers prefer to interact through digital platforms. Digital marketing strategies also provide many economic advantages because their costs are much more economical compared to traditional marketing strategies. Therefore, it is important for companies to understand and implement the right digital marketing strategies to remain competitive in an increasingly global and dynamic market.